Social Media Literacy Assistance to Ponorogo Instagram Admins as Citizen Journalism Activities - Marwantika, Asna Istya; Prabowo, Galih Akbar; Fauzi, Ahmanda Fitriyana (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Instagram administrators @ponorogo.update, @setenpo, @iloveponorogo, and @infoponorogo have played an active role in an organic movement of citizen journalists in Ponorogo. This Instagram admin has actively amplified Ponorogo locality-themed information that residents need, especially during the COVID-19 pandemic. Instagram in Ponorogo has been accessed with a high engagement rate. Besides that, the Instagram admin acts as a curator of information and has been able to determine the behavior patterns of netizens in Ponorogo. The social media literacy assistance service uses the Community-Based Participatory Research (CBPR) method, which consists of laying the foundation, planning research, gathering and data analysis, and acting on findings. The CBPR method is then synthesized with a theoretical framework for digital literacy levels. The result of this service program is that the Instagram Ponorogo admin and the service team succeeded in formulating a guidebook for managing Instagram as a medium for disseminating information on Ponorogo residents. This social media literacy guide booklet has been synchronized based on social media regulations and can be used applicatively. All stages of community service are practical strategic steps so that Ponorogo residents are accustomed to receiving credible and valid information (a well-informed society) and minimizing the occurrence of misinformation, disinformation, and hoaxes.